Slovenska katoliška cerkev in Karađorđevići - Griesser Pečar, Tamara (Studia Historica Slovenica, 2023)
When it became clear that the autonomy of the South Slavs within the Austro-Hungarian Empire was no longer feasible, the Slovenian Catholic Church supported unification with Serbia. The Karađorđević dynasty was alien to the Slovenes, also because it belonged to the Orthodox faith. In the Kingdom of SHS or Kingdom Yugoslavia were six officially recognized religions, the Catholic Church was only second to the Orthodox. For theat reason, a part of the political class was in favour of a republic and a federalist system – including the majority of the clergy, first and foremost the Bishop of Ljubljana, Anton B. Jeglič. The Catholic Church was facing a number of problems, both with diocesan and parish boundaries and the issue of the religious fund. She opposed the separation of Church and State, and saw problems in the educational and school spheres. The biggest problem was the agreement between the Kingdom and the Holy See. Although the Concordat was finally signed in 1935, it was never ratified by the Kingdom of Yugoslavia.
Keywords: Aleksander; catholic schools; cerkev; concordat; Jeglič, Anton Bonaventura; Karađorđević (rodbina); katoliške šole; king Aleksander I.; konkordat; Korošec, Anton; Kraljevina Jugoslavija; Kraljevina Srbov, Hrvatov in Slovencev; Orli; Sixth January dictatorship; Sokoli; unitary constitutional framework